Maternal Health Information Access and Utilization among Pregnant Women in Rural Communities of Jalingo, Taraba State, Nigeria - Idi, Shadrach (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
This study aimed to investigate how pregnant women in rural communities in Jalingo, Taraba State, access and utilise maternal health information, as well as the challenges they encounter in this process. Drawing from the health belief model, a qualitative approach was employed, involving in-depth interviews with 25 participants. The data collected were thematically analysed, and the findings revealed that pregnant women primarily access maternal health information from hospitals and clinics, gaining knowledge on childbirth preparation, nutrition, exercise, and pregnancy risks. However, they face challenges including overcrowded hospitals, poor staff attitudes, language barriers, and transportation issues. The study recommends that the government should improve its infrastructure and services in public hospitals and rural clinics to accommodate the large number of women seeking maternal health information and services, implement language interpretation services, utilise diverse information dissemination channels, establish mobile clinics to take maternal health services into rural communities, foster community awareness, and support networks for maternal health issues.